2018
DOI: 10.1016/j.scitotenv.2018.07.187
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Brevibacterium linens RS16 in Oryza sativa genotypes enhanced salinity resistance: Impacts on photosynthetic traits and foliar volatile emissions

Abstract: The emission of volatiles in response to salt stress in rice cultivars has not been studied much to date. Studies addressing the regulation of stress induced volatile emission by halotolerant plant growth promoting bacteria containing ACC (1-aminocyclopropane-1-carboxylate) deaminase are also limited. The objective of the present study was to investigate the salt alleviation potential of bacteria by regulating photosynthetic characteristics and volatile emissions in rice cultivars, and to compare the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 86 publications
(116 reference statements)
1
11
0
Order By: Relevance
“…In addition, the inoculated plants resulted in a 8.2%, 9.4%, and 7% increase in the plant dry weight compared to the non-inoculated plants under combined stress conditions at 3, 4, and 5 days after the stress imposition, respectively. Such an increase in the plant dry weight can be corroborated with previous studies in which the inoculation of B. linens RS16 was able to enhance the dry weight of rice [21] and canola [23] under salt stress conditions. In addition, B. linens RS16 has the ability to secrete hormones such as indole-acetic acid and cytokinins that are important for enhancing plant growth and for the ability to decrease stress ethylene levels through its ACC deaminase activity [23].…”
Section: Bacterial Inoculation Reduced Ethylene Emissions and Enhanced Plant Biomass Under Combined Uv-b Radiation And Heat Stressessupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, the inoculated plants resulted in a 8.2%, 9.4%, and 7% increase in the plant dry weight compared to the non-inoculated plants under combined stress conditions at 3, 4, and 5 days after the stress imposition, respectively. Such an increase in the plant dry weight can be corroborated with previous studies in which the inoculation of B. linens RS16 was able to enhance the dry weight of rice [21] and canola [23] under salt stress conditions. In addition, B. linens RS16 has the ability to secrete hormones such as indole-acetic acid and cytokinins that are important for enhancing plant growth and for the ability to decrease stress ethylene levels through its ACC deaminase activity [23].…”
Section: Bacterial Inoculation Reduced Ethylene Emissions and Enhanced Plant Biomass Under Combined Uv-b Radiation And Heat Stressessupporting
confidence: 88%
“…The use of ACC deaminase-producing, plant growth-promoting bacteria (PGPB) has shown promising results in the enhancement of plant growth and stress alleviation under various environmental conditions [20][21][22]. However, there have been a lack of studies that explore the effectiveness of bacterial inoculation in enhancing stress tolerance under combined UV-B radiation and heat stresses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased photosynthetic rates and decreased stomatal resistance enhanced the plant biomass of PGPR-inoculated pea plants ( Wang et al, 2016 ). An interesting study by Chatterjee et al (2018) found that treatment of rice plants with ACC deaminase-containing Brevibacterium linens RS16B decreased volatile organic compound (VOC) emissions and enhanced photosynthesis by reducing the availability of ACC and ACC oxidase activity, suggesting that research on volatile emissions during salt stress can reveal new insights related to stress severity and the initiation of secondary metabolism with stress progression. Ansari et al (2019) demonstrated that PGPR inoculation increased root length, chlorophyll pigments, leaf number, relative water content (RWC), stomatal conductance (gs), and photosynthesis rate (Pn) in alfalfa plants under salt stress.…”
Section: Modifications In Plant Physiological Statusmentioning
confidence: 99%
“…In agricultural production, besides genetic breeding of salt-tolerant varieties, improvement of cultivation conditions is an important strategy. For example, optimizing rhizosphere bacterial community has been demonstrated to efficiently enhance plant tolerance to salt stress (Chatterjee et al 2018a(Chatterjee et al , 2018b. Plant growth-promoting rhizobacteria (PGPR) are a group of soil microorganisms, either rhizospheric (free-living) and/or endophytic (in symbiotic association with plant root interior).…”
Section: Introductionmentioning
confidence: 99%